1992
DOI: 10.1016/0014-5793(92)80775-c
|View full text |Cite
|
Sign up to set email alerts
|

11 and Gαq guaninine nucleotide regulatory proteins differentially modulate the response to thyrotropin‐releasing hormone in Xenopus oocytes

Abstract: Xenopus ooeytes that express mouse thyrotropin-releusing hormone receptors (TRH-Rs) after injection if RNA transcribed from TRH-R eDNA respol~d to THR by a depolarizing current, This r,~sponse is transduced by activation of phosphoinositide-specifie phospholipase C and utilizes an as yet unidentified endogenous guanine nucleotidc-binding regulatory (G) protein(s), The g subunit of G;t and Gq have recently been shown to couple receptors to activation of phospholipase C. To determine whether there are functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 27 publications
2
8
1
Order By: Relevance
“…There has, however, been some controversy concerning the ability of G proteins of the G␣ q family to activate the PLC cascade in the oocytes. Our earlier study showed that responses are enhanced by injection of cRNA for G␣ q or G␣ 11 (21), but in other reports G␣ q or G␣ 11 injected into the oocyte has reduced Cl Ϫ currents (19,41). The results presented here support the idea that the G␣ subunit of all members of the G␣ q family can couple to GPCRs and activate the oocyte's IP 3 /Ca 2ϩ -induced Cl Ϫ conductance.…”
Section: G␣ 16 Inhibition Of Ligand-induced CLsupporting
confidence: 76%
“…There has, however, been some controversy concerning the ability of G proteins of the G␣ q family to activate the PLC cascade in the oocytes. Our earlier study showed that responses are enhanced by injection of cRNA for G␣ q or G␣ 11 (21), but in other reports G␣ q or G␣ 11 injected into the oocyte has reduced Cl Ϫ currents (19,41). The results presented here support the idea that the G␣ subunit of all members of the G␣ q family can couple to GPCRs and activate the oocyte's IP 3 /Ca 2ϩ -induced Cl Ϫ conductance.…”
Section: G␣ 16 Inhibition Of Ligand-induced CLsupporting
confidence: 76%
“…pear to have distinctly different f unctions after thyrotropinreleasing hormone or ␣ 1 -adrenergic receptor activation (Lipinsky et al, 1992;Macrez-Leprêtre et al, 1997). These studies, and our results, suggest that the coupling preferences suggested by in vitro and overexpression studies may not reflect those found in native cells.…”
Section: Discussioncontrasting
confidence: 39%
“…To address this question, we have used the Xenopus oocytes system to study receptor-G protein specificity in vivo. Coexpression of thyrotropin-releasing hormone receptors with either mouse G␣ q or G␣ 11 demonstrated different modulation of the response to thyrotropin-releasing hormone by each one of these G proteins (22). Applying the antisense approach, we demonstrated for the first time different coupling preferences of neuromedin B receptor for G␣ q and G␣ 11 (1).…”
mentioning
confidence: 89%